2015
DOI: 10.1002/cjce.22161
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional lattice Boltzmann simulation of natural convection in differentially heated square cavity: Effect of Prandtl and Rayleigh numbers

Abstract: A thermal lattice Boltzmann method is utilized for the numerical simulation of the natural convection heat transfer phenomena inside a differentially heated square cavity. Numerical simulations are performed to elucidate the combined effects of Prandtl number (0.71 ≤ Pr ≤ 100) and Rayleigh number (104 ≤ Ra ≤ 106) on heat transfer and fluid flow characteristics inside the cavity. Detailed insights are gained by the evaluation of isotherms, stream functions and vorticity profiles. For higher Prandtl and Rayleigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 61 publications
0
15
0
1
Order By: Relevance
“…1) are written as • The left wall (x=0) is considered as no-slip stationary wall. It is, however, partially heated isothermally (temperature T H ) for the fixed length of heating (l h =H/2) at either of the three (top, middle and bottom) locations, i.e., (5) where, the lengths h 1 and h 2 =(h 1 +l h ) are defined for the different cases ( …”
Section: Problem Statement and Mathematical Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…1) are written as • The left wall (x=0) is considered as no-slip stationary wall. It is, however, partially heated isothermally (temperature T H ) for the fixed length of heating (l h =H/2) at either of the three (top, middle and bottom) locations, i.e., (5) where, the lengths h 1 and h 2 =(h 1 +l h ) are defined for the different cases ( …”
Section: Problem Statement and Mathematical Modelingmentioning
confidence: 99%
“…The lattice Boltzmann equations (LBE) for the flow and thermal energy transports are written as follow: (23) where, the equilibrium distribution functions (f k eq and g k eq for the flow and thermal fields, respectively) are given as (24) (25) Here, Δt, Δx (=e k Δt), c (=Δx/Δt=1.0), u, T, e k and w k are lattice time step, lattice space step, lattice streaming speed, velocity vector, temperature, discrete velocity vector and equilibrium distribution of weight for direction k, respectively. The relaxation parameters (τ ν and τ g for the momentum and thermal energy transport fields, respectively) are defined as (26) (27) Under the assumptions that the buoyancy force is directly proportional to the temperature gradient and negligible radiative heat transfer, the Boussinesq approximation is accounted [5,34,47,48] by calculating the buoyancy force in the vertical direction as follow.…”
Section: -1 Basic Form Of Lbe For Flow and Thermal Energy Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kefayati et al [26] have explored the natural convection in an open ended cavity for three Prandtl numbers, but the vertical wall of cavity is completely heated. Recently, Gangawane et al [28] studied the influence of wide range of Prandtl number (0.71 ࣘ Pr ࣘ 100) and Rayleigh number (10 4 ࣘ Ra ࣘ 10 6 ) on heat transfer characteristics of differentially heated square cavity by using lattice Boltzmann method.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest absolute average percentage difference for the experimental and numerical temperature profiles was for the rk − ε t model and the highest was for the sk − ω model. Tables 1 and 2 represent the summary of available literature on the natural convection in open ended as well as differentially heated cavity with wall completely [19][20][21][22][23][24][25][26][27][28] and partially heated [29][30][31][32][33][34][35], respectively with their ranges of physical parameters. It can be concluded that from Tables 1 and 2 and aforementioned discussion that huge amount of the literature pertaining to the convection heat transfer characteristics from cavity with one wall completely heated is now available.…”
Section: Introductionmentioning
confidence: 99%